Hawaii Macadamia Nut Company - George H. Tompson; Dan Verreault; Holly B. Tompson (The Journal of Entrepreneurial Finance and Business Ventures, 2009)
Owners of the Hawaii Macadamia Nut Company (HMNC) are facing an expansion opportunity. A land owner has property available that would enable the HMNC to expand its acreage and revenue by about 20%. To fully consider this opportunity the owners must decide 1) whether the expansion is strategically and financially viable, 2) how to raise capital to finance the expansion, and 3) whether they have the skills to manage the company's growth during expansion. This is a case study describing a real company facing a real opportunity in Hawaii. The names of the company and its principals have been disguised.
Keywords: 650